In vitro cultured Neoparamoeba perurans causes amoebic gill disease in Atlantic salmon and fulfils Koch's postulates - Crosbie, PBB; Andrew Bridle; Karine Cadoret; Barbara Nowak (2012)
Amoebic gill disease (AGD) in marine farmed Atlantic salmon is of growing concern worldwide and remains a significant health issue for salmon growers in Australia. Until now the aetiological agent, Neoparamoeba perurans , has not been amenable to in vitro culture and therefore Koch’s postulates could not be fulfilled. The inability to culture the amoeba has been a limiting factor in the progression of research into AGD and required the maintenance of an on-going laboratory-based infection to supply infective material. Culture methods using malt yeast agar with sea water overlaid and subculturing every 3–4 days have resulted in the establishment of a clonal culture of N. perurans , designated clone 4. Identity of the amoeba was confirmed by PCR. After 70 days in culture clone 4 infected Atlantic salmon, causing AGD, and was re-isolated from the infected fish. Diagnosis was confirmed by histology and the infectious agent identified by PCR and in situ hybridisation using oligonucleotide primers and probes previously developed and specific to N. perurans . This study has fulfilled Koch’s postulates for N. perurans as a causative agent of AGD and illustrates its free-living and parasitic nature.